DAMPAK ELECTRONIC WORD OF MOUTH TERHADAP MINAT PEMBELIAN MAKANAN MENGGUNAKAN GO-FOOD DENGAN KEPERCAYAAN MEREK SEBAGAI FAKTOR MEDIASI - Saani Zahrotul Aen; Risma Nurhapsari; Kusumajaya, Robby Andika (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
This research was conducted with the aim of determining the impact of Electronic Word of Mouth on demand for food purchases using Go-Food with brand trust as an intervening variable. The sample in this study was 100 respondents obtained through a sampling technique using the simple random sampling method. The data collection method uses a questionnaire which is announced to respondents after which the data results are processed using SEM (Structural Equation Modeling) which is used in the SmartPLS V.4 analysis test. The results of this study show that the impact of electronic word of mouth has a positive effect on purchase intention, while brand trust has no effect on electronic word of mouth and interest in purchasing food using Go-Food among Uin Walisongo Semarang students.